Emergency obstetric care in a rural hospital: On-call specialists can manage C-sections - Shyam V Ashtekar; Madhav B Kulkarni; Ratna S Ashtekar; Vaishali S Sadavarte (Wolters Kluwer Medknow Publications, 2012)
Background: Institutional birth and Emergency Obstetric Care (EmOC) are important strategies of the National Rural Health Mission (NRHM). While the Community Health Center (CHC) is expected to serve EmOC needs in NRHM, the CHCs are hamstrung due to chronic shortage of specialist doctors. Alternative strategies are therefore needed for ensuring EmOC. Objectives: This study aims to estimate the EmOC needs in a private rural hospital from case records and find some useful predictors for caesarian section (C-section) and to assess C-section needs in the context of on-call specialist support. Materials and Methods: We analyzed a two-decade series of 2587 obstetric cases in a private rural hospital for normal deliveries and EmOC including C-section. Results: About 80% of the obstetric cases were normal deliveries. Of the remaining 20% cases that required EmOC, nearly one-third required C-section. In the series, two maternal deaths occurred due to hemorrhage. About 13% case records showed past abortion, which adds to EmOC workload. Primipararous mothers with higher age had a greater incidence (23%) of C-section. The C-section rate shows a steady rise from 3% to above 10% in the series. Conclusions : This rural hospital required C-section in 6.4% cases. This C-section workload was managed with the help of on-call specialists. The local hospital team could manage 93.6% of the cases and abortions with only two maternal deaths. This strategy of an on-call specialist team can be an option for CHCs till resident specialists are adequately available.